Promising practices connecting schools to families of children with special needs - Hiatt-Michael, Diana B. (Family, school, community, partnership., 2004)
Focusing on parent involvement in children's education in the USA, this volume covers such topics as: government support; parent-school communication; parent-child literacy projects; preparation for teachers; and parent centres.